Mesenchymal stem cells for the management of rheumatoid arthritis: immune modulation, repair or both?. Issue 2 (March 2017) - Ansboro, Sharon; Roelofs, Anke J.; De Bari, Cosimo
Abstract : Purpose of review: Mesenchymal stromal/stem cells (MSCs) have potent anti-inflammatory and immunomodulatory properties, in addition to their ability to form cartilage and bone. The purpose of this review is to highlight recent developments and current knowledge gaps in our understanding of the protective effects of MSCs against inflammatory arthritis, and to discuss their clinical exploitation for the treatment of rheumatoid arthritis (RA). Recent findings: The weight of evidence for protective mechanisms of exogenously administered MSCs is on immunomodulatory effects, including inhibition of dendritic cell maturation, polarization of macrophages to an anti-inflammatory phenotype, and activation of regulatory T cells, thereby dampening inflammation and preventing joint damage. Evidence for direct effects on tissue repair is scant. Recent studies have identified MSC subsets in vivo and an important question is whether MSCs in their native tissues have similar immunoregulatory functions. Recent proof-of-concept clinical studies have shown a satisfactory safety profile of allogeneic MSC therapy in RA patients with promising trends for clinical efficacy. Summary: Allogeneic MSCs could be effective in RA. Larger, multicentre clinical studies are needed to provide robust evidence, and MSC treatment at early stages of RA should be explored to 'reset' the immune system.